MOTIVATION OF FISH FARMERS IN DEVELOPING FISH CULTIVATION BUSINESSES IN THE VILLAGE SUKA MAJU RAMBAH SUB- DISTRICT, ROKAN HULU REGENCY, RIAU PROVINCE - Putri Mauliapita Gumelinsi; Kusai Kusai; Zulkarnain Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACT This research was conducted on may 2019 in Suka Maju Village, Rambah sub-District, Rokan Hulu Regency, Riau Province. This study aims to determine the characteristics of fish farmers. to find out how the level of motivation of fish farmers and to analyze how the characteristics relate to the motivation of fish cultivator businesses. The method used in this study is the survey method which is analyzed using Rank Spearman and the number of respondents in this study were 25 respondents. From the results of the research analysis, Farmers characteristics include: age, education, income, number of dependents and bussiness experience. From the results of the research analysis, it was found that the level of motivation of fish farmers is seen from 6 indicators namely 3 indicators of intrinsic motivation (willingness, hope, enthusiasm)and 3 indicators of extrinsic motivation (rewards, income, market opportunities), the more dominant indicator is the intrinsic motivation indicator with a score of 48%,and extrinsic motivation indicators 44%. The relationship of characteristics with the motivation of fish farmers stated, the relationship of intrinsic motivation related to age, education, and business experience has a significant relationship, the relationship between intrisic motivation with income and the number of family dependents is not significant. And extrinsic motivation relations related to age, education, number of family dependents and business experience have a significant relationship, the relationship between extrinsic motivation and income is not significant. Keywords: Relationships, characteristics, motivation business, fish farmer.